Design of a Two Resonating Coil WPT System for Portable Electronics Load - Priyadharshini. J; Sanjitha. S; Nandhakumar. T (Journal of Power Electronics and Devices, 2017)
Wireless power transmission (WPT) has been attracting a large vary of subjects in varied fields and additionally become an extremely active analysis space attributable to their potential in providing technology to our daily lives. The wireless power transmission are going to be necessary to use within the close to future as a result of this technology allows the transmission of electricity from an influence supply to an electrical load across an air gap while not interconnecting wires. During this paper, we stock out a pilot study to gift the present technologies of wireless power transmission, their recent technology also as its future trends. What is more, we tend to additionally describe lots of applications in wireless transmission.